Intelligent Transformation of Android Apps in Detecting and Mitigating Project Failure Risk Levels - Sayfuddin Sayfuddin; Surya Hadi (Eduvest - Journal of Universal Studies, 2025)
Building infrastructure plays an important role in the progress of a nation. However, failures in planning, design, construction, and maintenance can hinder development goals. The risk of failure of a construction project can come from technical aspects, human error, and natural factors. Indonesia, especially Lombok in West Nusa Tenggara, faces challenges in infrastructure sustainability, especially after being designated as a National Tourism destination through Presidential Decree No. 84/2021. Despite the increase in infrastructure development, many cases of construction failures still occur. This research aims to develop a digital transformation-based intelligent Android application that can detect and mitigate the risk of project failure. The study used a mixture of qualitative and quantitative methods, with the Likert scale for risk measurement. The first stage involved 22 respondents from several cases of project failure, resulting in 19 variables that caused failure. The second stage involved 88 respondents to test the validity and reliability of these variables, as well as analyze the level of risk using the Severity Index and Probability and Impact Matrix. The results of the study identified 19 risk factors, with 4 variables related to building failure and 15 variables related to construction failure implementation. Risk is classified into high, medium, and low categories, where 3 variables have high risk, 14 medium risk variables, and 2 low risk variables. This research also formulates risk management strategies, including steps to reduce and anticipate risks. In addition, the research resulted in the application of Risk Check Level, which aids in the detection, analysis.